Interplay of epilepsy and long-term potentiation: implications for memory - Marin-Castañeda, Luis A.; Pacheco Aispuro, Gerónimo; Gonzalez-Garibay, Guillermo; Martínez Zamora, Carlos Alejandro; Romo-Parra, Hector; Rubio-Osornio, Moisés; Rubio, Carmen (Frontiers in Neuroscience, 2025)
The interplay between long-term potentiation (LTP) and epilepsy represents a crucial facet in understanding synaptic plasticity and memory within neuroscience. LTP, a phenomenon characterized by a sustained increase in synaptic strength, is pivotal in learning and memory processes, particularly in the hippocampus. This review delves into the intricate relationship between LTP and epilepsy, exploring how alterations in synaptic plasticity mechanisms akin to those seen in LTP contribute to the hyperexcitable state of epilepsy. This state is conceptualized as a dysregulation between LTP and LTD (Long-term depression), leading to pathologically enhanced synaptic efficacy. Additionally, the role of neuroinflammation in both LTP and epilepsy is examined, highlighting how inflammatory mediators can influence synaptic plasticity. The dual role of neuroinflammatory pathways, enhancing or inhibiting LTP, is a focal area of ongoing research. The significance of various signaling pathways, including the MAPK, mTOR, and WNT/β-catenin pathways, in the modulation of synaptic plasticity and their relevance in both LTP and epilepsy. These pathways are instrumental in memory formation, consolidation, and epileptogenesis, illustrating a complex interaction between cellular mechanisms in the nervous system. Lastly, the role of calcium signaling in the relationship between LTP and epilepsy is scrutinized. Aberrant calcium signaling in epilepsy leads to an enhanced, yet pathologically altered, LTP. This dysregulation disrupts normal neural pathways, potentially leading to cognitive dysfunction, particularly in memory encoding and retrieval. The review emphasizes the need for targeted interventions in epilepsy that address cognitive functions alongside seizure control.